2019
DOI: 10.1101/755066
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The cyanobacterial saxitoxin exacerbates neural cell death and brain malformations induced by Zika virus

Abstract: 31The northeast (NE) region of Brazil commonly goes through drought periods, which 32 favor cyanobacterial blooms, capable of producing neurotoxins with implications for human 33 and animal health. The most severe dry spell in the history of Brazil occurred between 2012 34 and 2016. Coincidently, the highest incidence of microcephaly associated with the Zika virus 35 (ZIKV) outbreak was described in the NE region of Brazil during the same years. In this 36 work, we tested the hypothesis that saxitoxin (STX), a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…The presence of cyanobacteria is especially problematic in Northeastern Brazil as it is the rst place where the association between cyanobacterial blooms and human deaths due to water contamination by cyanotoxins was recorded [50,51]. Cyanobacterial blooms produce cyanotoxins, including saxitoxins, which likely has induced the Congenital Zika Syndrome (ZIKV) [52]. Recently, the ZIKV has emerged as a serious problem in this region, with a high index of microcephaly coinciding with extreme drought periods [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of cyanobacteria is especially problematic in Northeastern Brazil as it is the rst place where the association between cyanobacterial blooms and human deaths due to water contamination by cyanotoxins was recorded [50,51]. Cyanobacterial blooms produce cyanotoxins, including saxitoxins, which likely has induced the Congenital Zika Syndrome (ZIKV) [52]. Recently, the ZIKV has emerged as a serious problem in this region, with a high index of microcephaly coinciding with extreme drought periods [52].…”
Section: Discussionmentioning
confidence: 99%
“…Cyanobacterial blooms produce cyanotoxins, including saxitoxins, which likely has induced the Congenital Zika Syndrome (ZIKV) [52]. Recently, the ZIKV has emerged as a serious problem in this region, with a high index of microcephaly coinciding with extreme drought periods [52].…”
Section: Discussionmentioning
confidence: 99%
“…The experiments were composed by two factors (plants), three treatments (control, microcystin-LR and saxitoxin) with three levels (concentrations) (Figure 1). The microcystin-LR (MC-LR1= 0,4 µg/L; MC-LR2= 1,0 µg/L; MC-LR3= 5,0µg/L) and saxitoxin (SX-1= 0,02µg/L; SX-2= 0,1µg/L; SX-3= 0,4µg/L) concentrations selected for this study were more frequently observed in Brazilian Semiarid water bodies (Moura et al 2018, Pedrosa et al 2020, facilitating the comparison of the laboratorial studies with real case scenarios.Before the experiments, all seeds were sterilized with hypochlorite (0,1%) for 10 min and then washed with Ultra-pure water. Seeds of two plants were placed on double layer of Whatman Nº 1 filter paper as seed beds in petri dishes.…”
Section: Experimental Designmentioning
confidence: 97%
“…Neurotoxins are a group of compounds that have clear biological effects on the nervous system but differ in chemical structure and action (Rutkowska et al, 2019). Saxitoxins are found in marine dinoflagellates and freshwater cyanobacteria including Raphidiopsis raciborskii, a common specie in Brazilian water reservoirs (Huang and Zimba, 2019;Pedrosa et al, 2020). Saxtoxins cause VGSC blockage and also prolong gating of potassium channels, however, there are only few studies reported in the literature on the effects of cyanoabacterial saxitoxins on crops and plants (Corbel et al, 2014;Christensen and Khan, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, an ecological study found no correlation between the use of the larvicide pyriproxyfen in stored water and microcephaly among municipalities of the metropolitan region of Pernambuco, the epicenter of the Brazilian microcephaly epidemic (Albuquerque et al 2016). Interestingly, experiments in mouse models suggested that maternal diet protein restriction (Barbeito-Andrés et al 2020) and exposure to cyanobacterial saxitoxin through water intake (Pedrosa et al 2019) exacerbate brain malformations induced by ZIKV. In fact, CZS may have multiple environmental cofactors and may be influenced by ZIKV genetic factors, but the constellation of alleles of host genes involved in immune functions may also be important predictor of the occurrence and severity of CZS.…”
Section: Fig 2 Machine Learning Approach and Genetic Czs/microcephamentioning
confidence: 99%